Improving Short Term Memory Through the Brain Gym Method - Sajodin Sajodin; Perla Yualita; Riandi Alfin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The elderly people face a decline in all physical functions as they age, as well as an increased risk of disease and other health issues such as short-term memory loss. Brain gym, a collection of simple movements that aims to unite the mind and body, is one of the sports aiming at maintaining and improving the quality of life. The purpose of this PkM activity was to socialize the brain gym and improve the elderly's short-term memory. The methods of implementing this activity were as follows: first, a situation analysis on activity partners was performed; second, a pretest was performed by measuring short-term memory using the HVLT instrument; third, the brain gym was implemented twice a week for three weeks; and fourth, at the end of the activity, a post-test and activity evaluation were performed. This activity was attended by 25 elderly people, and the results showed a 56.50 percent increase in pre-test and post-test scores. Because the data was not normally distributed, the Wilcoxon test was performed with the results indicating that the number the number 0.001 <0.05. It can be concluded that Brain Gym has a significant effect on the elderly's short-term memory. This increase in short-term memory occurred because brain gym movements increase blood circulation to the brain and stimulate the hemispheres to activate, thereby increasing thinking ability. The conclusion of this activity is that doing brain gym twice a week for three weeks can improve short-term memory, so it is suggested that the elderly do brain gym to maintain and improve their short-term memory